Metamodel independence in domain specific modeling languages - Irazábal, Jerónimo; Pons, Claudia Fabiana (2013)
Domain-specific modeling languages can simplify the development of complex software systems by providing domain-specific abstractions for modeling the system and its evolution in a precise but simple and concise way. In this work we elaborate on the notion of domain specific model manipulation language, that is to say a model manipulation language tailored to a specific domain. In contrast to well-known model manipulation languages, such as EOL or ATL, the language syntax and semantics are directly related to a specific domain and/or kind of manipulation, making manipulation easier to write and understand. Furthermore, we show how additional languages can be defined for the same domain and we discuss about implementation alternatives achieving complete platform-independence. We illustrate the proposal through a practical example in the domain of workout plans.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Software and Data Technologies : 7th International Conference, ICSOFT 2012, Rome, Italy, July 24-27, 2012, Revised Selected Papers. Berlín : Springer, 2013. (Communications in Computer and Information Science ; 411), pp. 140-154
Keywords: LENGUAJES DE DOMINIO ESPECÍFICO - DSL; TRANSFORMACIÓN DE MODELOS; INGENIERÍA DE SOFTWARE DIRIGIDA POR MODELOS - MDE